Evaluation of science and technology programs: from theory to practice and proposal of evaluation methods and criteria compatible with Vietnam’s conditions - Ngoc, Tran Hau; Chien, Nguyen Ngoc; Huy, Nguyen Quoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
Evaluation is an essential tool for effective management practices, evaluation is not only a tool to measure the success of the program but also contributes to that success. Evaluation helps program managers to plan, evaluate and demonstrate what their goals are to be achieved, decide how to add resources, how to modify and redesign the program, and adapt implemented in the next stage. Evaluation of the science and technology (S&T) program is usually done in 4 phases: (i) Ex-ante Evaluation: the assessment is conducted prior to program execution. This phase assesses the feasibility and quality of the program design; (ii) Mid-term Evaluation: the assessment is conducted midway through program implementation to review performance from inception and recommend necessary modifications; (iii) Terminal Evaluation: the assessment is carried out right after the end of the program, in order to consider the results achieved and summarize the entire implementation process, to draw the necessary experience as a basis for making the program acceptance report; (iv) Impact Evaluation: the assessment is carried out at an appropriate time, since the program was put into operation and used to clarify the effectiveness, sustainability and socio-economic impact of the program. Therefore, depending on the requirements, the purpose, process and method of evaluation will be different. In this article, we present the experiences of some countries in evaluating the S&T Program, and proposing evaluation of the program under conditions in Vietnam. Code: <span style="text-align: left; color: #000000; text-transform: none; text-indent: 0px; letter-spacing: normal; font-size: 14px; font-variant: normal; font-weight: 400; text-decoration: none; word-spacing: 0px; white-space: normal; orphans: 2; -webkit-text-stroke-width: 0px; background-color: #ffffff;">20082801